Towards industrialization of perovskite solar cells using slot die coating. Issue 18 (7th April 2020) - Verma, Anand; Martineau, David; Hack, Erwin; Makha, Mohammed; Turner, Erik; Nüesch, Frank; Heier, Jakob
Abstract : Carbon-based hole transport layer-free mesoscopic perovskite solar cells can be manufactured at industrially relevant speeds on large areas using slot die coating. The cells show efficiencies comparable to those manufactured by screen printing. Abstract : Carbon-based hole transport layer-free carbon mesoscopic perovskite solar cells (MPSCs) are considered to be cell architectures with high potential for commercialization, due to their enhanced stability. In the standard process for large area and module fabrication, mesoporous layers of TiO2, ZrO2 and carbon are screen printed onto fluorine doped tin oxide (FTO) coated with a compact TiO2 (cTiO2 ) layer. In this work, we sequentially replaced screen printing by slot die coating one by one for all layers until we achieved a fully slot die coated solar cell. Slot die coating is a manufacturing technique with a much higher throughput than screen printing. We demonstrate that slot die coated layers need not be sintered separately as opposed to the screen printed layers, but can rather be co-fired for increased manufacturing speed and efficacy. We characterize the inks, coating process, morphology and performance of these solar cells. The cells show efficiencies comparable to those of the screen printed control devices. The cells also show extraordinarily high shelf life stability. We also demonstrate that ellipsometry can be used as an efficient (in-situ) tool to characterize the stack structure of the cells.